Identificação e caracterização parcial de receptores endógenos de lectinas de sementes da subtribo Diocleinae - Oliveira, Cláudia Martins de (2007)
The lectins constitute a special class of protein with the special propriety of reversibly and specifically interacting with carbohydrates and glycoconjugates. This lectins ability suggests a relevant in vivo biological role, but this hypothesis demands the existence of endogenous receptors. The intensification of research on receptors molecules may help to elucidate the lectins biological functions [...]